Introduction and Editorial Content of Journal Contemporary Private Law (vol. 1) - Rodrigues Junior, Otavio Luiz (Revista de Direito Civil Contemporâneo, 2014)
Introduction and Editorial Content of Journal Contemporary Private Law (full text)